2011 International Conference on Parallel Processing 2011
DOI: 10.1109/icpp.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

UnSync: A Soft Error Resilient Redundant Multicore Architecture

Abstract: Abstract-Reducing device dimensions, increasing transistor densities, and smaller timing windows, expose the vulnerability of processors to soft errors induced by charge carrying particles. Since these factors are only consequences of the inevitable advancement in processor technology, the industry has been forced to improve reliability on general purpose Chip Multiprocessors (CMPs). With the availability of increased hardware resources, redundancy based techniques are the most promising methods to eradicate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Second, the overhead of each processor core will contribute to the overall overhead of the entire multi-core system. As a result, recent research has suggested that the problem of soft-error resilience in multi-core systems needs to be approached from an orthogonal perspective [Jey11]; this means the approach should consider redundancy of different resources during the soft-error mitigation procedure.…”
Section: State-of-the-art Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, the overhead of each processor core will contribute to the overall overhead of the entire multi-core system. As a result, recent research has suggested that the problem of soft-error resilience in multi-core systems needs to be approached from an orthogonal perspective [Jey11]; this means the approach should consider redundancy of different resources during the soft-error mitigation procedure.…”
Section: State-of-the-art Methodsmentioning
confidence: 99%
“…Another state-of-the-art method has been proposed in [Jey11]. It is a promising method which is called Unsync.…”
Section: State-of-the-art Methodsmentioning
confidence: 99%
See 3 more Smart Citations